Ion channels in human erythroblasts. Modulation by erythropoietin. - Cheung, J Y (1992)
To investigate the mechanism of intracellular Ca2+ ([Cai]) increase in human burst-forming unit-erythroid-derived erythroblasts by erythropoietin, we measured [Cai] with digital video imaging, cellular phosphoinositides with high performance liquid chromatography, and plasma membrane potential and currents with whole cell patch clamp. Chelation of extracellular free Ca2+ abolished [Cai] increase induced by erythropoietin. In addition, the levels of inositol-1,4,5-trisphosphate did not increase in erythropoietin-treated erythroblasts. These results indicate that in erythropoietin-stimulated cells, Ca2+ influx rather than intracellular Ca2+ mobilization was responsible for [Cai] rise. Both Ni2+ and moderately high doses of nifedipine blocked [Cai] increase, suggesting involvement of ion channels. Resting membrane potential in human erythroblasts was -10.9 +/- 1.0 mV and was not affected by erythropoietin, suggesting erythropoietin modulated a voltage-independent ion channel permeable to Ca2+. No voltage-dependent ion channel but a Ca(2+)-activated K+ channel was detected in human erythroblasts. The magnitude of erythropoietin-induced [Cai] increase, however, was insufficient to open Ca(2+)-activated K+ channels. Our data suggest erythropoietin modulated a voltage-independent ion channel permeable to Ca2+, resulting in sustained increases in [Cai].